Vanessa Siddle Walker: Honoring Keepers of Knowledge by Using Their Stories to Improve Education - Melissa Holmes; Eileen Wertzberger; Kay Ann Taylor; Lori Goodson (Educational Considerations, 2020)
Dr. Vanessa Siddle Walker, a renowned historical researcher in the field of education, is a leading voice in the history of school desegregation in the United States. In this interview, she discusses positioning black educators as significant agents of change in the collective narrative of schools and highlights how their organized action and strategic advocacy has led to social justice and equity for black students. Her research informs how our schools have worked in the past, and how lessons from our past can serve to mobilize resources for the equitable education of all children today.
Keywords: Historical research; desegregation; AERA; Georgia Teachers Association; social justice